IMPLEMENTASI FIREWALL FILTER RULES UNTUK KEAMANAN JARINGAN DAN METODE QUEUE TREE UNTUK MANAJEMEN BANDWIDTH PADA MIKROTIK - Silvia Wulandari Situngkir; Sanri Yuliana Siallagan; Asri Angel Tumanggor; Dedy Kiswanto (LPPM Universitas Dhyana Pura, 2025)
Currently, almost all sectors of life such as offices, government agencies, educational institutions, and public services depend on the internet network as a means of supporting work and information exchange media. Optimal internet utilization can increase productivity. However, high internet usage needs to be balanced with effective bandwidth management. Unstructured bandwidth management can cause a decrease in internet access speed. In addition, network security aspects are also crucial in the implementation of computer networks. Negligence in this aspect can open a gap to network attacks or hacking. Therefore, a reliable firewall system is needed to support good network quality. One solution to overcome these problems is to implement a firewall and queue tree method using MikroTik devices. This approach can increase network performance and improve internet service quality. With proper grouping and restriction of data traffic, network usage becomes more controllable, reduces the risk of bandwidth overload, and creates a more secure and equitable network environment. The implementation was carried out using a MikroTik RB941-2nD router and Winbox software, with configurations that included router settings, filter rules, and queue trees. The results of the implementation show that bandwidth management and filtering access to sites containing adult content and online gambling can run effectively.